CUTI SUAMI DALAM RUU KIA UNTUK MENDAMPINGI ISTERI MELAHIRKAN PERSPEKTIF HIFẒ AL-NASL DAN POLITIK ETIS PEMERINTAH - Busyro; Ismail; Gusril Basir; Fajrul Wadi; Rahmiati; Sindi Sinora (Universitas Islam Negeri Mataram, 2023)
The plan of providing 40-day-paternity leave is just waiting for discussion and ratification into law. On the one hand, the RUU KIA (Maternal and Child Health bill (MCH bill) can guarantee the fulfillment of some of mothers’ and children’s rights if they are accompanied by the head of the family during the birth process. However, on the other hand, the status of the husbands who also work for government or private companies requires them to complete the workload, and 40 days of leave is considered a long time for workers to leave. This study aims at examining the implementation of the concept of hifẓ al-nasl on the ethical politics of government concerning the birth of the RUU KIA. This writing is library research by which the data sources were obtained from documents, books, journals, and news on social media. The data were analyzed by using a qualitative approach. The conclusion of this study showed that the philosophical basis of the 40-day-paternity leave policy is a crystallization of the concept of protecting wives and prospective babies and in accordance with the objectives of Islamic law in providing protection for offspring (hifẓ al-nasl). This government’s ethical politics is also an implementation of the rule of taṣarruful imām `alā ra'iyat manūṭun bil maṣlaḥah (policies taken by the government must be ensured to gain benefit for the people).